Economic Efficiency Measure of Induction Motors for Industrial Applications - Keerti Rai; S B L Seksena; A N Thakur (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper, introduced an expression of Economic Efficiency Measure (EEM) to permit quick evaluation for replacement of faulty induction motor with alternative (new or refurbished motor) for lowest life-cycle cost based on efficiency and rated-load conditions. This approach, simplifies the process for evaluating the energy efficiency to mere proportionate factor called as EEM. During the operating phase, the motor losses correspond to extra energy consumption, based on various parameters like motor operating conditions, operating hours, operating costs, fault factor, depreciation factor and fixed costs.  The approach is effective in addressing the global issue on replacement of the faulty motor that needs a comprehensive analysis and mathematical expression. Compared to other alternatives the EEM provides a simple but effective and reliable means to asses, the feasibility of replacing or refurbishing the faulty motor. A detail analysis here would establish how much the present approach is effective in determining the replacement for a faulty induction motor either by a new one or refurbished one of corresponding rating.